Vitamin D Enhances Radiosensitivity of Colorectal Cancer by Reversing Epithelial-Mesenchymal Transition - Yu, Xinyue; Wang, Qian; Liu, Baocai; Zhang, Ning; Cheng, Guanghui (Frontiers in Cell and Developmental Biology, 2021)
Colorectal cancer (CRC) is often resistant to conventional therapies. Previous studies have reported the anticancer effects of vitamin D in several cancers, its role in radiotherapy remains unknown. We found that 1α,25-dihydroxyvitamin D3 (VD3), the biologically active form of vitamin D, had antitumor effects in CRC and sensitized CRC cells to ionizing radiation (IR). VD3 demonstrated synergistic effect in combination with IR, detected by colony formation and cell proliferation assays. Combination treatment was associated with various phenotypes, including apoptosis, autophagy, and epithelial-mesenchymal transition (EMT). Using proteomics, “regulation of cell migration” and “cadherin” were found to be obviously enriched in GO terms, and enrichment of differentially expressed proteins was significantly associated with the EMT phenotype, with cystatin D and plasminogen activator inhibitor-1 (PAI-1) the two promising candidate proteins. We confirmed that siRNAs of cystatin D and PAI-1 reversed the radiosensitization effect of VD3, accompanied with enhanced migratory and invasive capabilities of SW480 cells. Mechanistically, cystatin D and PAI-1 partially interfered with the JAK/STAT3 and TGF-β/Smad3 signaling pathway as determined by proteomics. Furthermore, treatment with IR plus VD3 significantly suppressed tumor growth in xenograft CRC models without additional toxicity to normal tissues. Our study reveals that VD3 enhances radiation sensitivity both in vitro and in vivo in CRC, and provides a novel insight for improving the radiotherapy efficacy in CRC.